2019
DOI: 10.1161/atvbaha.118.311576
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Mechanisms of Vascular Calcification in Aging

Abstract: Approximately 20% of the world’s population will be around or above 65 years of age by the next decade. Out of these, 40% are suspected to have cardiovascular diseases as a cause of mortality. Arteriosclerosis, characterized by increased vascular calcification, impairing Windkessel effect and tissue perfusion, and determining end-organ damage, is a hallmark of vascular pathology in the elderly population. Risk factors accumulated during aging affect the normal physiological and vascular aging process, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 126 publications
1
91
1
1
Order By: Relevance
“…In this way, atherosclerosis, as well as aging or age-related atherosclerosis, causes vascular wall senescence and, as a consequence, VC-the final step of the pathology process. Increased VC in atherosclerosis produces numerous marked vascular effects, such as a reduction of tissue perfusion, which eventually causes end-organ damage, particularly in the elderly population [125].…”
Section: Hif and Atherosclerosismentioning
confidence: 99%
“…In this way, atherosclerosis, as well as aging or age-related atherosclerosis, causes vascular wall senescence and, as a consequence, VC-the final step of the pathology process. Increased VC in atherosclerosis produces numerous marked vascular effects, such as a reduction of tissue perfusion, which eventually causes end-organ damage, particularly in the elderly population [125].…”
Section: Hif and Atherosclerosismentioning
confidence: 99%
“…Numerous studies have shown that risk factors accumulating during aging contribute to VSMC osteogenic differentiation and vascular calcification, such as increased levels of the cyclin-dependent kinase inhibitors p16 and p21, extracellular matrix remodelingrelated collagen deposition and elastin degradation, impaired DNA and increased levels of prelamin A and reactive oxygen species, and matrix vesicles released by injured endothelium [2][3][4][5]. Recently, reduced levels of aging-related calcification inhibitors such as matrix γcarboxyglutamic acid (Gla) protein (MGP), anti-aging and anti-calcification factor α-klotho and sirtuin 1 (sirt1), were found to greatly promote vascular calcification [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research showed that exogenous IMD1-53 may attenuate CKD-associated vascular calcification by upregulating α-klotho and vitamin D3 plus nicotine (VDN)-induced vascular calcification by increasing MGP in young rats [6,7]. In addition, IMD1-53 treatment could improve vascular function by increasing endothelial nitric oxide synthase activity [25] and inhibiting reactive oxygen species production [26], which may affect vascular aging [4]. However, whether IMD inhibits aging-associated vascular calcification is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Aging attributes to vascular calcification through multifaceted mechanisms [19]. Several researchers reported similar results that advanced age and FBG were independently related to aortic calcification in non-rheumatic population [20][21][22][23].…”
Section: Discussionmentioning
confidence: 92%